2014
DOI: 10.1007/s00253-013-5491-8
|View full text |Cite
|
Sign up to set email alerts
|

Effective mutations in a high redox potential laccase from Pleurotus ostreatus

Abstract: Since the first report on a laccase, there has been a notable development in the interest towards this class of enzymes, highlighted from the number of scientific papers and patents about them. At the same time, interest in exploiting laccases-mainly high redox potential-for various functions has been growing exponentially over the last 10 years. Despite decades of work, the molecular determinants of the redox potential are far to be fully understood. For this reason, interest in tuning laccase redox potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 55 publications
2
29
0
Order By: Relevance
“…However, data on kinetic parameters of this enzyme (38) showed this not to be the case, suggesting that the redox potential difference between the T1 copper and the substrate may not be the only factor that contributes to substrate oxidation. It has also been reported that a variant of the Pleurotus ostreatus laccase (1H6C) which showed a higher redox potential (by ϩ0.12 V) relative to the wild-type enzyme exhibited catalytic efficiencies similar to those of the wild type on several substrates (39). Our studies, as reported here, also show that while the mutant laccase variants exhibited redox potentials similar to those of WtLcc, they exhibited different catalytic properties from those of the parent enzyme.…”
Section: Discussionsupporting
confidence: 71%
“…However, data on kinetic parameters of this enzyme (38) showed this not to be the case, suggesting that the redox potential difference between the T1 copper and the substrate may not be the only factor that contributes to substrate oxidation. It has also been reported that a variant of the Pleurotus ostreatus laccase (1H6C) which showed a higher redox potential (by ϩ0.12 V) relative to the wild-type enzyme exhibited catalytic efficiencies similar to those of the wild type on several substrates (39). Our studies, as reported here, also show that while the mutant laccase variants exhibited redox potentials similar to those of WtLcc, they exhibited different catalytic properties from those of the parent enzyme.…”
Section: Discussionsupporting
confidence: 71%
“…Among these redox potentials, the redox potential of the T1 site is a key parameter for substrate specificity of the enzyme, since the higher the laccase redox potential is, the wider the range of oxidised substrates (Macellaro et al 2014). In other words, the catalytic efficiency of laccases for some reducing substrates depends linearly on the redox potential of the T1 copper, meaning that the higher the potential of the T1 site the higher the catalytic efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…From an electrochemical point of view, all laccases can be divided in three categories depending on the copper T1: high-, medium-and lowpotential enzymes, depending on plant or fungal source of laccases (Morozova et al 2007). The conservation of the redox potential of the T2 site to around 400 mV versus NHE would require that the structure of the T2 redox centres in laccases was conserved in terms of ligands and copper-ligand distances (Macellaro et al 2014). The middle category is composed of laccases from basidiomycetes, for example Myceliophtora thermophila, basidiomycete C30, Rhizoctonia solany, Coprinus cinereus, with potentials in the range 470-710 mV.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, increasing the redox potential of the T1 copper is not straightforward and it does not guarantee success. [36][37][38][39] Therefore, the reactive-like pose depicted in Fig. 3 was selected as the initial template for the design, aiming at improving the enzyme-substrate interaction energy of such a binding mode, hence its statistical importance in the active site.…”
Section: 5-dabsamentioning
confidence: 99%